The 2020 Pandemic in the Theoretical Debate in International Relations - Bosoer, Fabián; Turzi, Mariano (Geopolítica(s). Revista de estudios sobre espacio y poder, 2020)
Can we re-read the geopolitical framework provided by authors like Robert Kaplan and Robert Kagan to think of the COVID-19 pandemic as an “environmental problem” that guides / determines the political action of nation states? This article presents some of its main topics in order to analyze the impacts of the health crisis that affected the entire planet, contrasting the perspective of conservative deterministic geopolitics with a reading of critical geopolitics.
Keywords: COVID-19 pandemic; Malthusianism; globalization; environment; health crisis